(3OjhGf GHf GdfbjHs - (3GHf GdfbjH , YHO GdQMef Hf eMeO Hf ceGd GdOjf eMeO GdMSjfj, GHf GdfbjH,J (B1081 (3g` s ((3CMeO Hf eMeO GdMehj s)
(3ChdgG (B:s
(3MjG GdUHG hfYjeg EP fMf fQJY aj afGFg s
(3BNQgG (B:s
(3CHjJ hGdhLO aj bdHj MHGdg QSi CfOH eUGHj hCMHGHj YghOj fSi s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B109 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B191s
Keywords: (3GdCOHs